Examining the factors that affect women in land accessibility amongst Talensi of Northern Ghana - Ba–an, Maxwell Tengolzor; Dery, Dominic Alimbey; Segbefia, Samuel Kwabla; Agbenyo, John Stephen; Kpeleku, Alberta (Research Journal in Advanced Social Sciences, 2022)
Agricultural production provides a source of income for millions of families throughout Africa. Women, who constitute the majority and are the poorest in Africa, and particularly those in Talensi in Ghana, are engaged in farming and make significant contributions to agricultural production. Whether or not women have access to land will determine their contributions to the agricultural sector and any other sectors of the economic system. This study investigated factors that affect women's access to land in the Talensi community in Northern Ghana, using a qualitative approach that included in-depth interviews and key informant interviews. The findings were presented in a report. A total of 30 participants from the Talensi area were questioned, including chiefs, Tindans, women, and household heads. The findings of the study covered customary practises on property ownership and inheritance, economic considerations, understanding of land rights, and urbanisation in the Talensi area. According to the findings, future land reforms should involve increased engagement with traditional leaders (gate keepers) to rethink the modalities of getting access to and control over property to be successful.